Analyzing the Strategy for Promoting Religious Moderation Values Among Activists of the Campus Islamic Da'wah Association in Malang City - Yusuf, Zulfikar; Mukhlis, Fahrudin (Universitas Islam Negeri Raden Intan Lampung, 2024)
The idea of religious moderation has received a lot of attention from academics lately; in 2019, the Indonesian Ministry of Religion released a book bearing a similar title. But the concept of religious moderation has generated mixed responses; some even think that those who practice it are not truly practicing their religion or are not honest in their views. An organization called Campus Da'wah Association (LDK) aims to spread Islam and is almost always present in universities. With this broadcasting responsibility, LDK will probably realize this vision. On the other hand, LDK is more often associated with extremist organizations that have a more conservative understanding of Islam. For this reason, the purpose of this study is to discover what the activists at the Campus Da'wah Institute think about religious moderation. This research uses a case study design in conjunction with a qualitative technique. The research object is the general chairman and the chairman of the cadre division of the Campus Da'wah Association. After that, the researcher used documentation, observation, and interviews. The techniques offered by Miles and Huberman were used by researchers to analyze data. In addition to data validity regulations, researchers employed triangulation techniques. The outcomes of the study show how strongly LDK officials adhere to religious moderation. They are ready to help put the concept of religious moderation into practice both personally and professionally. Numerous attempts have been made to implement projects that align with this ideology. They regret it, though, when some disparage other groups that have different viewpoints and think theirs is the most rational and accurate.